FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT TERHADAP PEMILIHAN JASA PELAYANAN KESEHATAN DI KECEMATAN LATIMOJONG TAHUN 2016 - Lestari Lorna Lolo; Ny. Julma (Voice of Midwifery, 2016)
Health services are any efforts that are held personal or together within an organization to maintain and improve health, prevent, and cure diseases and restore the health of individuals, families, groups, or society. Buntu Sarek villageis is one village in the village Latimojong district with the general state of the topografi. Buntu Sarek village is a plateau area and the hills and located at an altitude between 600-2500 m above sea level. Health services are always concentrated in urban areas alone and while it was preliminary study found the lack of utilization of health care services in the district Latimojong reasons long distances and can still be treated traditionally.The aims of the research to analyze the factors that influence decision of communities on the selection of a health care services in Latimojong district 2016. Descriptive analytic design with cross sectional study approach, the number of respondents as many as 61 heads of families who are assigned using method simple random sampling . Data collected by a questionnaire and analyzed using univariate and bivariate using Chi-Square statistical test.Conclusion of the research was prove there are significant influence on the distance of health care services selection (p= 0.006), there is a significant influence on the culture of health care services selection (p = 0.000) and there is significant effect on the information of health care services selection (p= 0.000). Suggestions in this research will wish governments and communities work together, care services in Latimojong district, so that people have the ability to reach quality health services and obtain health insurance.Key words : Distance, Culture, Information, Health Care Services Selection